Participatory approaches in the context of research into workplace health promotion to improve physical activity levels and reduce sedentary behaviour among office-based workers: protocol for a scoping review. Issue 12 (30th December 2021) - Buffey, Aidan John; Carson, Brian; Donnelly, Alan; Salsberg, Jon
Abstract : Introduction: Physical activity (PA) workplace health promotion (WHP) interventions have traditionally used a top-down research approach where end-users are considered as passive subjects. Whereas participatory research (PR) involves the end-users within the research process utilising a bottom-up approach which allows the integration of the researcher's expertise and the end-users lived experiences, which has been shown to aid in the acceptability and relevance of the research. This protocol describes a scoping review which will explore, identify and map PR techniques and their impact when used in office-based WHP interventions designed to improve PA and reduce sedentary behaviour levels. Methods and analysis: This scoping review will follow the guidelines and framework proposed by Levac et al and Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. Articles will be retrieved via five databases: Web of Science, PubMed, Scopus, Google Scholar and OpenGrey, searching from 1 January 1995, to the date of search in 2022. A search strategy was piloted, to identify appropriate keywords and MeSH terms. Two independent reviewers will screen retrieved articles based on our inclusion and exclusion criteria by title and abstract first, followed by the full text. Our key inclusion criteria relating to our population, intervention, comparison, outcome framework will be to include studies which focused on office-based working adults and that the PA WHP took a PR approach. Articles written in non-English languages will be excluded. Any discrepancies will be discussed until a consensus is reached. Data will be extracted, charted and summarised via a narrative synthesis and qualitative thematic analyses. Ethics and dissemination: Ethical approval was not required for this scoping review. The completed scoping review findings will be disseminated in a peer-reviewed journal which has a research scope that encompasses PR and WHP. The findings will be presented at appropriate academic conferences and to project partners to inform the design of a WHP intervention.